STUDY OF HOMOGENEITY, POROSITY AND INTERNAL DEFECTS IN AERATED AND EPS AGGREGATE POLY BRICKS USING NEUTRON RADIOGRAPHY TECHNIQUE - Alam, Khurshed; Rahman, Md. Sayeedur; Rahman, Md. Mostafizur; Islam, S. M. Azaharul (JOURNAL OF ADVANCES IN PHYSICS, 2015)
A powerful non-destructive testing (NDT) technique is adopted to study the internal defects and elemental distribution/homogeneity and porosity of aerated brick and EPS aggregate poly brick samples. In the present study the internal defects like homogeneity, porosity, elemental distribution, EPS aggregate and aerator distributor in the test samples have been observed by the measurement of gray value/optical density of the neutron radiographic images of these samples. From this measurement it is found that the neutron intensity/optical density variation with the pixel distance of the AOI of the NR images in both expanded polystyrene (EPS) aggregate poly brick and aerated brick samples comply almost same in nature with respect to the whole AOI but individually each AOI shows different nature from one AOI to another and it confirms that the elemental distribution within a AOI is almost homogeneous. Finally it was concluded that homogeneity, elemental distribution in the EPS aggregate poly brick sample is better than that of the aerated brick sample.